1994
DOI: 10.2527/1994.7282022x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lecithin on the apparent ileal and overall digestibility of crude fat and fatty acids in pigs

Abstract: Four barrows of approximately 40 kg initial body weight, fitted with post-valvular T-cecum cannulas, were used to study the effect of lecithin as an external emulsifier on apparent ileal and overall digestibility of crude fat, fatty acids, and other dietary nutrients (DM, N, GE, crude fiber [CF], P, Ca, and Mg), as well as the utilization of N, GE, Ca, P, and Mg. Two levels of lecithin (0 and .24%) and two levels of rendered fat (0 and 6%) in cereal-soybean meal-based diets were investigated according to a 4 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Bayley and Lewis 4 found higher fat digestibilities of tallow (10% in diet) by using the emulsifier Lissapol N (nonylphenol ethylene oxide condensate). With rendered fat (6% in diet) or soy oil (6% in diet), Øverland et al 7,8 did not find any improvement in ileal or faecal fat digestibility from lecithin supplementation (0.2-2% in diet). It has been speculated that, with unhydrolysed lecithin, mixed micelles might become abnormally large, slowing up the diffusion process through the unstirred layer and reducing micellar fatty acid uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Bayley and Lewis 4 found higher fat digestibilities of tallow (10% in diet) by using the emulsifier Lissapol N (nonylphenol ethylene oxide condensate). With rendered fat (6% in diet) or soy oil (6% in diet), Øverland et al 7,8 did not find any improvement in ileal or faecal fat digestibility from lecithin supplementation (0.2-2% in diet). It has been speculated that, with unhydrolysed lecithin, mixed micelles might become abnormally large, slowing up the diffusion process through the unstirred layer and reducing micellar fatty acid uptake.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this study was to determine the apparent metabolizable energy (AME n ) values of LEC, ASS and GLY, as well as their mixture in a proportion that resembles their individual proportion in the original crude soy oil (Nelson & Cox, 2002;Overland et al, 1994;Vieira et al, 2002).…”
Section: Energy Utilization Of By-products From the Soybean Oil Indusmentioning
confidence: 99%
“…Lecithin is removed by centrifuging crude soy oil, representing around 1.5 to 3.1 % of the original source (Overland et al, 1994). As for its use by the animal, LEC has important roles in the phosphate and energy metabolism, in addition of being an important source of choline (Menten et al, 1997;Woerfel et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The possible explanation for these results might be the results of more retention and absorption of both calcium and fatty acids. Conversely, the reports earlier have showed that high calcium supplementation resulted in more formation of calcium soap (Atteh and Leeson, 1983) and no effect of dietary lecithin on fat and calcium diestibility (Overland et al, 1993(Overland et al, , 1994.…”
Section: Discussionmentioning
confidence: 85%
“…Although there was no treatment effect on fat digestibility, higher value of fat absorption might reduce fermentation in the small intestine resulting in lower villous surface damage and subsequently might improve growth performance. However, some previous research has demonstrated that there was no influence of lecithin on the utilisation of fat (Overland et al, 1994), but the method of addition of lecithin to the diet might play a role in these differences.…”
Section: Discussionmentioning
confidence: 86%